Translating God: Derrida, Ricoeur, Kearney - Lynn Sebastian Purcell (University of Calgary, 2012)
The purpose of the present essay is to defend two related notions. The more specific notion that I seek to defend is Richard Kearneyâ€™s conception of God as posse, of God as a possible God. His position has recently been criticized for three separate reasons: that it is not radical enough, that it is crypto-metaphysical, and that it forecloses the most profound aims of ethics. At a broader level what seems to be at stake is the opposition between partisans of radical finitude, those who hold that the most profound questions are encountered at the limits of thought, and an alternative â€œinfiniteâ€ conception that Kearney shares with Paul Ricoeur, which maintains that fidelity to unpredictable events opens the way to what is most profound about the human condition. In response I argue that the criticisms fail to hit their mark because they presuppose a broadly Derridian or post-modern position in order to make their argument, when it is just those presuppositions that are in question.